Kreativitas Guru Al Quran Hadis Menggunakan Media Pembelajaran Audio Visual Dalam Meningkatkan Hasil Belajar - Indra Syah Putra; Nurmisdaramayani Nurmisdaramayani ; Julia Satifa (Reslaj : Religion Education Social Laa Roiba Journal, 2019)
The problem found in the research is that during the learning and teaching process in madrasas, the Al-Qur'an Hadith teachers have not involved students directly with the application of the digital Al-Qur'an, so students have not been trained in solving various learning problems. The unavailability of media that supports learning and teaching activities of Al-Qur'an Hadith in madrasas. This type of research is qualitative with a field research approach. Sources of data as informants are school principals and teachers of the Qur'an Hadith, data collection methods by means of observation, interviews and documentation. The results of the study found that the application of audio-visual media in Al-Quran Hadith subjects had been maximally applied in connection with the implementation of learning in the COVID-19 pandemic which required online learning and teaching activities. So, learning using audio-visual media is very appropriate to be applied in MTs. Tarbiyah Waladiyah Pulau Banyak. And the application of audio-visual media in improving the ability to understand the learning of the Qur'an and Hadith for class VII MTs students. Tarbiyah Waladiyah Pulau Banyak has been carried out well and there has been an increase since the beginning of the pre-meeting, namely the number of students who get a complete score, namely 29.7% of students who get a complete score in the field of study of the Qur'an and Hadith, at the first meeting it increases to 46% of students who complete in Al-Quran Hadith learning activities on the material to understand the short letter of the Qur'an. At the second meeting the level of completeness of students in learning the Qur'an Hadith was 78.3% of class VII MTs. Private Tarbiyah Waladiyah. Then analyzed from Meeting III, student completeness reached 100%. Keywords: Audio Visual Media, Learning Outcomes